Standardization of 30 Gross Tonnage (GT) Danish Seiner. Issue 1 (January 2021) - Pamungkas, R S; Purwanto, H; Sunardi,
Abstract: Cantrang – Danish Seiner is growing rapidly in the north coast of Java Seas-Fisheries Management Area 712. In recent year, there have been many issues regarding the prohibition operation of seiner fishing gear impact sustainable fisheries, Cantrang owners and fishermen livelihood due to the regulation of fishing gear and the mark down of Gross Tonnage measurement. This research attempt to obtain preliminary data on Danish seiner operating in Indonesia, as set base design for 30 GT Danish seiner standard includes the scope of the principal dimensions of the seiner, main engine powering and the layout of deck for fishing operations. The method uses purposive sampling of 30 GT Cantrang, number of population 148 Cantrang of 30 GT at 4 regencies; Tegal, Batang, Rembang and Pati. The result of this research are the main measurement value - the ratio of principal dimension, main engine power, and deck area and Cantrang Danish seiner operation. The standardized 30 GT Cantrang has the following maximum main dimensions: Length (L) = 18.21 meters, Width (B) = 6.58 meters and Deck Height (D) = 2.00 meters with L / B ratio = 3.29-3.33, L / D = 11.2 - 2.74, B / D = 3.96-4.26. The main engine power 1 engine 160-190 HP and for 2 engines 2 × 120 HP. The deck area of 70-80 m 2 significantly impacts Cantrang fishing gear operation